MERLO, E - MERLO,E (Tufts Archival Research Center, 2007)
Note for Karen Moog, Derek Crawford, Ted Lattanzio, Jim, Lance Pressl, and James Spector from Ellen Merlo suggesting ways to involve Ira Magaziner in the Federal Excise Tax (FET) issue. Suggests ways to convince him including putting together packets of information with the Canadian and Wharton economic Models.